Purpose Driven Internet Use and Its Impact on Academic Performance of College Students - Waweru, Aida W.; Gichugu, Martin (Journal of Education and Training, 2022)
The purpose of this study was to determine how students in Middle-Level Colleges use the internet, with a special focus on the Nairobi Institute of Business Studies (NIBS). The study was conducted using a descriptive research approach. The student population was determined using a purposive sample strategy, while the stratified sampling approach was utilized to divide the population into distinct subgroups (strata) based on the eight courses that students took. Both open-ended and closed-ended questionnaires were used to collect relevant data. The questionnaire was tested for validity and reliability in a group of randomly selected students. Following data collection, descriptive statistics were used to examine pertinent data. To summarize the data and report the research findings, descriptive statistics such as percentages, frequencies, bar graphs, and pie charts were used. This research focused on the NIBS College, which has approximately 3000 regular students. A total of 138 people were sampled from the population to participate in the study. The majority of students, according to the report, use the internet for entertainment. For communication and pleasure, students utilize social networking sites like Facebook and Twitter at nearly the same rates. The respondents also stated that using the internet has expanded their access to more up-to-date educational information and has had a good impact on their academic efficiency. When compared to traditional materials, respondents found the Internet to be more informative. The respondents also said that the internet saved time and provided reliable information. To access the internet, most students possess and use smartphones (iPhones). They use the internet in their dorms compared to other locations on campus or at home, where internet access was unreliable. The majority of students preferred Google to other Internet services. This demonstrated that students rely extensively on Google to find current and relevant information. The vast majority believed that people do not need to be trained on how to use the internet to find information. The trial-and-error method was the most prevalent strategy for obtaining relevant Internet skills. Others sought advice from their peers or took official training given by several computer colleges to learn how to utilize the internet.